IMPROVING STUDENTS’ READING ABILITY IN NARRATIVE TEXT BY USING CIRC TECHNIQUE AT THE FIRST GRADE IN ACADEMIC YEAR 2016/2017 OF MAN KRECEK PARE - Satriandi, Egi (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Reading is one of the important skill that must be mastered by students of Islamic senior high school to support their learning. However, there are many students still get low score in reading. Researcher in MAN Krecek Pare finds it. From 40 students, there are 19% students could be said pass KKM. Based on the fact founded the researcher tried to use CIRC technique to improve students reading ability especially in the first class of second semester of language class. The researcher found the result of students in reading skill has improved although it is not significant and also researcher see activities in learning process run well although many students not focus. In the first cycle, there are 45, 00% students could achieve the passing grade. However, in the two cycle students could achieve the passing grade are 82, 50%. Therefore, the result indicated that there was founded the improvement before and after using CIRC technique. It can be seen from the first cycle 45, 00% and the second cycle 82, 50%. In addition, students’ motivation in learning English especially reading skill has improved. Based on the result activity, the researcher assumes that CIRC technique can improve the students’ ability in studying. It is good to the English teacher to use this technique in teaching and learning process reading. It is able to motivate the students, and make the enjoyable teaching and learning situation in order to stimulate the students’ creativity and activity in the teaching and learning process.